PHARMACOLOGICAL REACTIVITY OF RAT VAS-DEFERENS IN CHRONIC AND SUBACUTE LEAD-INTOXICATION - Kempinas, W. G.; Pereira, OCM; Melo, V. R.; Carvalho, TLL (Comparative Toxicology Lab Kansas State Univ, 1991)
The influence of subacute and chronic lead intoxication on the responsiveness of the rat vas deferens was investigated by determining pD2 and relative responsiveness ratio (p) values for noradrenaline and for acetylcholine. Thus, the pD2 values of noradrenaline and acetylcholine from vas deferens of lead-treated rats were greater than those from normal rats, indicating that lead, in the dose and periods of treatment utilized, provoked a rise in vas deferens sensibility to noradrenaline and acetylcholine. Since it is known that the cirurgical or chemical denervation of the sexual ducts also provokes hypersensitivity, it may be suggested that this would be a possible mechanism for the observed alterations. A local lead toxic effect on the smooth muscle or at the level of androgen receptors should also be considered.